Causal Model of quality of campus community, Student Value and Academic Civility - fahimeh keshavarzi; rahmatallh Marzooghi; elham heidari (Journal of Medical Education and Development, 2020)
Introduction: The purpose of the present study was to investigate the causal model of quality of campus community, Student Value and Academic Civility Students of Shiraz University of Medical Sciences. Methods: The research method was descriptive correlational method. The research sample consisted of 338 students of Shiraz University of Medical Sciences who were selected by cluster random sampling method. The Research tools was College and University Community Inventory (Ernest Boyer, 1990), student value (Dziewanowska, 2017) and academic civility (Clark & Springer, 2017). Data obtained from questionnaires were evaluated in both descriptive and inferential sections using statistical tests by spss21 and lisrel8.54 software. By implementing the structural equation model, it was found that the proposed model has a good fit and the students' scientific etiquette is well predicted and explained through the quality of the university environment. Result: The findings showed that the quality of campus community has a positive and significant effect on academic civility (p-value<0.001). The quality of campus community has a positive and significant effect on student value (p-value<0.001). The findings showed that the student value by mediation the quality of campus community could affect the academic civility students (p-value<0.001). Students 'values also play a mediating role in the relationship between the quality of the university environment and students' academic civility. Conclusion: Values determine the desirable path of students’ life especially in the final years of their studies, therefore, students obtained necessary motivation based on a set of values which is internalized in them and attempt to achieve their great goals. Hence, it is necessary to provide important measures for the development of higher education environment and also to provide the basis for the internalization of values in students with the aim of their education and literacy toward the desired goal and perfection. Keywords: quality of campus community, Student Value, Academic Civility, student, Shiraz University.